Effect of polypropylene fibre on cementitious mortar early shrinkage cracking using the eccentric-ring test - Abusogi, Maha A.; Muda, Zakaria Che; Hafez, Mohamed Ahmed; Bakri, Mudthir (Frontiers in Materials, 2023)
The effects of polypropylene fibres on mortar and cement-paste cracking were investigated using different amounts of fibre fractions and eccentric rings under restrained-shrinkage conditions. Eccentric-ring tests were conducted to investigate early-age shrinkage cracks. The characteristics of restricted cementitious materials were described by evaluating the cracking time and using concrete mixtures that are less likely to crack. Different fibre-volume fractions significantly enhanced the width, area, and age of cracking. Increasing the water-cement ratio and sand percentage increased the cracking age. The eccentric-ring test showed a greater susceptibility to cracking in cement-mortar composites. The mechanical strength was assessed, and the impact of polypropylene fibres was investigated.